The Application of the Assignment Method to the Integrated Writing Ability of the Circ Method in View of the Use of Learning Media - Nani Nani (Indonesian Journal of Basic Education, 2022)
This research is an action research of using different learning media. The CIRC method is applied by using image media and concept map chart media.The general objective of this research is to prove which students have better writing skills: (1) students who undergo learning using Task-Based Learning Methods, (2) students who undergo learning using pictorial media and concept map chart media, (3 ) students who undergo learning using the CIRC image media method and CIRC concept map media, (4) students who undergo learning using task-based concept map media, (5) students who undergo learning using illustrated media CIRC methods and media methods task-based pictures, and (6) students who take part in writing lessons using concept map media. Data was collected using a written test. Furthermore, data were collected in the form of tables and graphs, which were then analyzed. The data analysis method used in this study. conclusions can be drawn from this study. First, students who study using the CIRC method have better writing skills than students who study using the task-based method. Second, students who learn by using picture media have less developed writing skills than students who learn by using concept map media